La « Grande-Syrie », diachronie d’une construction géographique (1912-1923) - Julie Andurain (d’) (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: As Edward Said once showed, the East was at least partially created by the West, both on a semantic level and on a geographical level. The prolegomena of the war in Syria do not wait for the great Arab revolt or the Sykes-Picot agreements to take shape. Virtually, they are present in the definitions of "Great Syria" which appear as early as 1912, in an oriental context. During the war, this term, raised to the rank of geographical concept, functions as an intellectual and political tool intended to compete with Great Britain. Soon the Arab and Turkish elites seized it to challenge it or to adopt it with another political aim, reason why the war did not end in the East until 1923.A diachronic analysis of the term "Great Syria" reveals the successive geographical contours of Syria, and shows the necessity of adopting another chronological framework than that of 1914-1918, in order to apprehend war in the East.